Preparing the Field for Feasibility Testing of a Parenting Intervention for War‐Affected Mothers in Northern Uganda. Issue 2 (26th October 2015) - Wieling, Elizabeth; Mehus, Christopher; Yumbul, Cigdem; Möllerherm, Julia; Ertl, Verena; Laura, Achan; Forgatch, Marion; Neuner, Frank; Catani, Claudia
Abstract : In this article, we discuss the successful implementation of an adapted evidence‐based parenting intervention for families affected by two decades of war in Northern Uganda. The adaptation and adoption of such interventions to support mental health and family functioning is widely endorsed by prevention scientists and considered a priority in global mental health. The preparation and early adoption phases of engaging with a highly vulnerable community affected by war trauma are documented in this paper along with a discussion of the steps taken to adapt a parenting intervention for cultural and contextual fit. This study is a component of an overall program of research aimed at reducing the long‐term negative effects of war on parenting practices and childhood outcomes, which have considerable implications for preventing mental, neurological, and substance‐use disorders. The processes described here cover a 4‐year period culminating in the implementation of the nine‐session Enhancing Family Connection intervention piloted with a group of 14 mothers. The lessons in cultural adaptation have been valuable and the feasibility results promising for further testing the intervention.